A review of the genus Bronchocela Kaup, 1827 (Reptilia: Agamidae) in the Nicobar Archipelago with the description of two new species - Chandramouli, S.r.; Adhikari, Omkar D.; Amarasinghe, A.a. Thasun; Abinawanto, A. (Zootaxa, 2023)
Species of the agamid genus Bronchocela Kaup, 1827 in the Andaman and Nicobar Islands are reassessed based on newly collected specimens from different parts of the Nicobar Archipelago. An assessment based on morphology and distribution of the identified groups reveal two new, unnamed populations, one allied to B. cristatella and the other allied to B. danieli. These two populations are described as new species, and Bronchocela cristatella is redescribed based on Sundaic specimens. The remaining species, B. danieli and B. rubrigularis are redescribed. Distributions of all of these four species are mapped and recommendations on their conservation status are suggested.